Biodiversity loss through speciation collapse: Mechanisms, warning signals, and possible rescue*. (29th April 2019) - Zhang, Lai; Thibert‐Plante, Xavier; Ripa, Jörgen; Svanbäck, Richard; Brännström, Åke
Abstract: Speciation is the process that generates biodiversity, but recent empirical findings show that it can also fail, leading to the collapse of two incipient species into one. Here, we elucidate the mechanisms behind speciation collapse using a stochastic individual‐based model with explicit genetics. We investigate the impact of two types of environmental disturbance: deteriorated visual conditions, which reduce foraging ability and impede mate choice, and environmental homogenization, which restructures ecological niches. We find that: (1) Species pairs can collapse into a variety of forms including new species pairs, monomorphic or polymorphic generalists, or single specialists. Notably, polymorphic generalist forms may be a transient stage to a monomorphic population; (2) Environmental restoration enables species pairs to reemerge from single generalist forms, but not from single specialist forms; (3) Speciation collapse is up to four orders of magnitude faster than speciation, while the reemergence of species pairs can be as slow as de novo speciation; (4) Although speciation collapse can be predicted from either demographic, phenotypic, or genetic signals, observations of phenotypic changes allow the most general and robust warning signal of speciation collapse. We conclude that factors altering ecological niches can reduce biodiversity by reshaping the ecosystem's evolutionary attractors.